Spatial Frames of Reference and an Investigation of Their Representations in Turkish - Ata Atak; Gülsün Leyla Uzun (Dilbilim Araştırmaları Dergisi, 2019)
This study was carried out to answer what kind of representations in Turkish could be obtained on spatial frames of reference. In the experiment which was conducted to determine spatial frames of reference used in Turkish, four different production tasks consisting of two object arrangements which indicate localization were done by total 80 participants 40 of whom were female and 40 of whom were male. This study presents a discussion based on the data which were obtained from the production tasks by the participants.